Beneficial Soil Bacterium Pseudomonas frederiksbergensis OS261 Augments Salt Tolerance and Promotes Red Pepper Plant Growth - Chatterjee, Poulami; Samaddar, Sandipan; Anandham, Rangasamy; Kang, Yeongyeong; Kim, Kiyoon; Selvakumar, Gopal; Sa, Tongmin (Frontiers in Plant Science, 2017)
Soil salinity, being a part of natural ecosystems, is an increasing problem in agricultural soils throughout the world. Pseudomonas frederiksbergensis OS261 has already been proved to be an effective bio-inoculant for enhancing cold stress tolerance in plants however its effect on salt stress tolerance is unknown. The main aim of the present study was to elucidate Pseudomonas frederiksbergensis OS261 mediated salt stress tolerance in red pepper. The plants were exposed to a salt stress using NaCl at the concentrations of 50 mM, 100 mM and 150 mM after twelve days of transplantation, while plant growth and enzyme activity were estimated fifty days after sowing. The height in P. frederiksbergensis OS261 inoculated plants was significantly increased by 19.05%, 34.35%, 57.25%, and 61.07% compared to un-inoculated controls at 0 mM, 50 mM, 100 mM and 150 mM of NaCl concentrations respectively under greenhouse conditions. The dry biomass of the plants increased by 31.97%, 37.47%, 62.67%, and 67.84% under 0 mM, 50 mM, 100 mM and 150 mM of NaCl concentrations respectively. A high emission of ethylene was observed in un-inoculated red pepper plants under salinity stress. P. frederiksbergensis OS261 inoculation significantly reduced ethylene emission by 20.03%, 18.01%, and 20.07% at 50 mM, 100 mM and 150 mM of NaCl concentrations respectively. Furthermore, the activity of antioxidant enzymes (ascorbate peroxidase, superoxide dismutase, and catalase) also varied in the inoculated red pepper plants. Salt stress resistance in the bacterized plants was evident from the improved antioxidant activity in leaf tissues and the decreased hydrogen ion concentration. Thus, we conclude that P. frederiksbergensis OS261 possesses stress mitigating property which can enhance plant growth under high soil salinity by reducing the emission of ethylene and regulating antioxidant enzymes.